Life cycle assessment of animal-based foods and plant-based protein-rich alternatives: a socio-economic perspective - Varela Ortega, C.; Blanco‐Gutiérrez, I.; Manners, Rhys; Detzel, A. (Wiley, 2022)
BACKGROUND Extensive research shows that replacing animal protein with plant-based protein in the diet would strongly alleviate the environmental impact of the food system. However, much less attention has been given to the socio-economic considerations of dietary transitions. This study analyses the socio-economic performance of innovative legume-based food prototypes, developed in the Protein2Food research project, and conventional animal-based products (chicken meat and dairy milk). We implement a social life cycle assessment (sLCA) to quantify and compare their potential socio-economic impacts along the entire life cycle.